From dwindling ice to headwater lakes: could dams replace glaciers in the European Alps?. (20th May 2016) - Farinotti, Daniel; Pistocchi, Alberto; Huss, Matthias
Abstract: The potential exploitation of areas becoming ice-free in response to ongoing climate change has rarely been addressed, although it could be of interest from the water management perspective. Here we present an estimate for the potential of mitigating projected changes in seasonal water availability from melting glaciers by managing runoff through reservoirs. For the European Alps we estimate that by the end of the century, such a strategy could offset up to 65% of the expected summer-runoff changes from presently glacierized surfaces. A first-order approach suggests that the retention volume potentially available in the areas becoming deglacierized is in excess of the volume required for achieving the maximal possible mitigation by more than one order of magnitude. Obviously, however, such a strategy cannot compensate for the reduction in annual runoff caused by glacier ice depletion. Our estimates indicate that by 2070–2099, 0.73 ± 0.67 km 3 a −1 of this non-renewable component of the water cycle could be missing in Alpine water supplies.